Equity in neurogenomics: advancing Parkinson’s disease research in AfrAbia - Wael Mohamed (Academia Molecular Biology and Genomics)
One of the most prevalent and debilitating neurodegenerative disorders worldwide is Parkinson’s disease (PD). Nevertheless, the majority of genomic insights and therapeutic advancements have been disproportionately focused on populations of European ancestry, resulting in a critical knowledge deficit in under-represented regions such as AfrAbia—a culturally and genetically wealthy convergence of Africa and the Arab world. This review emphasises the pressing necessity of prioritising equity in neurogenomics by incorporating a variety of genomic data and translational frameworks within AfrAbian populations. We investigate the role of population-specific genetic variation, environmental exposures, and ancestral backgrounds in the development, progression, and therapeutic response to Parkinson’s disease. We emphasise the opportunities and challenges associated with the development of equitable, context-sensitive research frameworks by delineating the region’s current genomic resources, ongoing research initiatives, and emerging biobank infrastructures. The review also addresses the role of consortia like the AfrAbia PD Genomic Consortium in democratising neurogenomic discovery, as well as capacity development, ethical considerations, and cross-border collaborations. In addition to promoting inclusion, the bridging of the equity gap in PD genomics also improves the scientific rigour and global relevance of the struggle against neurodegeneration.